2019
DOI: 10.1002/jcb.29299
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNAs in the regulation of insulin signaling pathway with respect to metabolic and mitogenic cascades: A review

Abstract: Insulin resistance (IR) is a shared pathological condition among type 2 diabetes, obesity, cardiovascular disease, and other metabolic disorders. It is growing significantly all over the world and consequently, a substantial effort is needed for developing the potential novel diagnostics and therapeutics. An insulin signaling pathway is tightly modulated by different mechanisms including the epigenetic modifications. Today, a deal of great attention has been shifted towards the regulatory role of noncoding RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 174 publications
0
18
0
1
Order By: Relevance
“… 7–9 miRNA analogs are attractive drug candidates because the simultaneous modulation of many target genes by a single miRNA analog may provide effective therapies for complex diseases such as diabetes, obesity and NAFLD. 10 For instance, several miRNAs have been implicated in the regulation of insulin signaling, 11 mitochondrial functions and obesity. 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 7–9 miRNA analogs are attractive drug candidates because the simultaneous modulation of many target genes by a single miRNA analog may provide effective therapies for complex diseases such as diabetes, obesity and NAFLD. 10 For instance, several miRNAs have been implicated in the regulation of insulin signaling, 11 mitochondrial functions and obesity. 12 …”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] miRNA analogs are attractive drug candidates because the simultaneous modulation of many target genes by a single miRNA analog may provide effective therapies for complex diseases such as diabetes, obesity and NAFLD. 10 For instance, several miRNAs have been implicated in the regulation of insulin signaling, 11 mitochondrial functions and obesity. 12 In both mouse models and human subjects, the activation of beige adipocytes is associated with several metabolic benefits, such as reduced obesity, diminished lipotoxicity and increased insulin sensitivity.…”
mentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small noncoding RNAs, which are considered as key regulators of gene expression at the posttranscriptional level and multiple pathophysiological processes [7,8]. Accumulated studies have strongly suggested miRNAs are essential in regulating pancreatic β cell functions, the release of insulin, and insulin resistance [9].…”
Section: Introductionmentioning
confidence: 99%
“…[ 54 ] reported that reduced levels of miRNA-146a were associated with IR in Type 2 diabetic patients. Some studies have shown that miRNA-146a may reduce insulin resistance by activating JNK and P38 MAPK pathways which can play a major role in insulin signaling pathway [ 60 , 61 ]. However, as we mentioned, more investigations are needed to extract the exact mechanism in this regard.…”
Section: Discussionmentioning
confidence: 99%